2021
DOI: 10.47992/ijcsbe.2581.6942.0132
|View full text |Cite
|
Sign up to set email alerts
|

A Technical Approach for Promotion of Yakshagana - A Literature Survey

Abstract: Background/Purpose: Yakshagana is a theatre style that combines varieties of make-up styles and dressing styles depending on the type of character or role that is to be played on the stage. This article briefly discusses certain areas of Yakshagana where technology can be used for object detection and make-up recognition to classify and identify the characters. Objective: The main objective of this literature survey is to summarize the techniques used to identify different objects in a Yakahagana image & t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In their comprehensive survey, Murthy and Nethravathi [16] examined the existing literature on Yakshagana, an immensely popular folk theatre form in coastal districts. Their findings shed light on the current state of Yakshagana education in the region, highlighting a significant gap in the emphasis placed on different aspects of the art form.…”
Section: Related Workmentioning
confidence: 99%
“…In their comprehensive survey, Murthy and Nethravathi [16] examined the existing literature on Yakshagana, an immensely popular folk theatre form in coastal districts. Their findings shed light on the current state of Yakshagana education in the region, highlighting a significant gap in the emphasis placed on different aspects of the art form.…”
Section: Related Workmentioning
confidence: 99%
“…Murthy and Nethravathi [16] conducted a literature survey on Yakshagana, a popular folk theatre form in coastal districts. They observed that while many educational institutions in the region offer Yakshagana as an additional course, the focus is mainly on teaching himmela and dancing steps, with little attention given to dressing and makeup styles.…”
Section: Introductionmentioning
confidence: 99%
“…Murthy and Nethravathi [1] conducted a literature survey on Yakshagana, a popular folk theatre form in coastal districts. They observed that while many educational institutions in the region offer Yakshagana as an additional course, the focus is mainly on teaching himmela and dancing steps, with little attention given to dressing and makeup styles.…”
Section: Introductionmentioning
confidence: 99%